Tuning the Morphology of Spray-Dried Supraparticles: Effects of Building Block Size and Concentration - Zhou, Huanhuan; Pujales Paradela, Rosa; Groppe, Philipp; Wintzheimer, Susanne; Mandel, Karl (Particle & Particle Systems Characterization, 2022)
Tuning the morphology of supraparticles can crucially influence their final properties and is, thus, important for their application in chemical, pharmaceutical, and food industries. The present study reveals how varied nanoparticle sizes, concentrations, and weight ratios in multicomponent dispersions influence the morphology of supraparticles assembled by these nanoparticle building blocks via spray-drying. In a droplet containing monodisperse nanoparticles, smaller nanoparticles form a coherent elastic shell due to lower cohesive forces. As the solvent enclosed in the shell evaporates less easily due to the narrow pores between the nanoparticles, this ultimately results in rather non-spherical supraparticles, while larger nanoparticles tend to yield spherical supraparticles. When small nanoparticles outweigh large ones in binary or trinary dispersions, the small nanoparticles form the outer shell that shrinks into a mushroom cap-like shape upon drying of the spray-droplet, while larger nanoparticles stay in the center of the droplet, resulting in non-spherical supraparticles. Furthermore, the findings give a more systematic insight into structures that potentially arise from multimodal-sized building blocks, thus, paving the way to tune the supraparticle morphology upon spray-drying, when working with more complex, multicomponent dispersions.
CRIS-Team WoS Importer:2022-09-23